Factores de riesgo para el desarrollo de trastornos del control de impulsos en sujetos mexicanos con enfermedad de Parkinson. - Lira-Juarez, Luisa G.; Domínguez-García, Ariadna; Rodríguez-Violante, Mayela; Cervantes-Arriaga, Amin; Santiago-de la Cruz, Elba C.; Medrano-Delgado, Angeles; Hernández-Medrano, Ana J.; Regalado-Mustafá, Andrés Y.; De La Rosa-Patlan, Giovanni E. (Archivos de Neurociencias)
Background: Impulse control disorders (ICDs) are behaviors that are performed repeatedly to the point of interfering with the patient's functionality and daily life, without regard for their consequences and with the sole purpose of obtaining immediate gratification. ICDs have been related to dopaminergic treatment. objective: To analyze the association of different risk factors for the development of ICD in the Mexican population. Methods: A cross-sectional study was carried out. The data collected affects the years 2021 to 2023. Data were collected through structured interviews including age, gender, year of symptom onset, year of diagnosis, levodopa equivalent dose, and antiparkinsonian treatment, and history of smoking and alcohol use was evaluated. results: A total of 244 patients diagnosed with Parkinson's disease (PD) were included, of whom 146 (59.8%) were men and 98 (40.2%) were women. The mean age was 63 ± 12.10 years. A total of 35 (14.3%) patients with ICD (ICD-PD) were found; the non-ICD group included 209 subjects (85.7%). When analyzing antiparkinsonian drugs, a higher use of dopamine agonists was found in the ICD group but did not reach statistical significance (p = 0.078). Only the variable alcoholism was identified as a risk factor in the logistic regression, as can be seen in its p = 0.034, the odds ratio value IS 2.55, indicating that patients with alcoholism have a 2.5 times higher risk of developing ICD. The rest of the variables did not show statistically significant p-values. conclusion: History of alcohol use was the main associated risk factor with the development of ICD.